VERBAL COLLOCATIONS IN THE SPOKEN ALBANIAN CORPUS IN KOSOVO - Baftiu, Adelajda; Rugova, Bardh (Ezikov svât, 2023)
This paper aims to examine verbal collocation in the spoken corpus of Albanian in Kosovo. Lexical and semantic components that are repeated in a linguistic context are known as collocations. The verbal collocations occurring inside the parameters of the sentence will be examined in this study. The most common verbs found in the corpus, those used more than 70 times, are used as the basis for this study. Examples include: vij, bëj, dal, hyj, marr and rri. Except for the verbs rri and hyj which came out with 16 meanings, the same verbs were presented with more than 30 meanings in the Dictionary of the Albanian Language. Due to their wide range of meanings and ditransitive nature, the verbs marr and bëj are used in the most consistent collocations. So, they are more likely to be followed by a complement unlike the verbs rri, hyj, dal and vij. The work makes a connection between corpus linguistics and semantics. The methods of Baker (2010) and Sinclair (1991) are applied in this investigation. They base their strategy on how frequently the words x and y are displayed next to one another, setting a spacing of five words to the left and five words to the right of the word x. 76 recordings of speakers from various cities in Kosovo make up the corpus of this study. The Partitur Editor application is used to transcribe recordings. The KWIC program is then used to automatically extract collocations as well as vocabulary from the transcriptions.